THE USE OF MOVING PICTURES IN TEACHING VOCABULARY IN TK TUNAS RIMBA 1 PEMALANG IN 2006/2007 ACADEMIC YEAR - SETYARINI, DEWI (2007)
The objective of this study is to find out the way's to overcome the students' problems in vocabulary mastery in order that (1) To know the effectiveness of teaching vocabulary using moving pictures at TK Tunas Rimba 1 Pemalang, (2) To find the strengths and weaknesses of teaching vocabulary using moving pictures at TK Tunas Rimba 1 Pemalang. The writer conducted a classroom action research from August 22 to August 27, 2006 at a class. There were 42 students as the sample. In this research, the writer taught vocabulary using moving picture. She took the vocabulary using moving picture. She took the vocabularies from Disney's Magic English volume 9, 10, 22, and 23 which are appropriate with the material presented in the curriculum. The writer conducted 4 cycle of action. The result of the action showed that after the writer conducted the action, the students' vocabulary mastery in higher that before. It can be seen from the result of both the observation of the students' activities during the actions and their mean of oral test in every action. The conclusion is teaching vocabulary using moving pictures at TK Tunas Rimba 1 Pemalang yields good result. Using moving pictures in teaching vocabulary is very effective in teaching learning process. The strengths of using moving pictures in tv are: (1) The students can remember and grasp the meaning of the words easily, (2) the students can use and pronounce words correctly, and (3) the students are motivated to learn English. The use moving pictures also have weakness : (1) to spend much money to get the material like, to buy CD Disney's magic English, to prepare pictures and real object, (2) needed more energy to teaching vocabulary in demonstrates the real object, needed another teacher to manage the class to be effective.